Search for direct CP violation in D0 → h−h+ modes using semileptonic B decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2013)
A search for direct CP violation in D0→h−h+ (where h=K or π) is presented using data corresponding to an integrated luminosity of 1.0 fb−1 collected in 2011 by LHCb in pp collisions at a centre-of-mass energy of 7 TeV. The analysis uses D0 mesons produced in inclusive semileptonic b-hadron decays to the D0μX final state, where the charge of the accompanying muon is used to tag the flavour of the D0 meson. The difference in the CP-violating asymmetries between the two decay channels is measured to beΔACP=ACP(K−K+)−ACP(π−π+)=(0.49±0.30(stat)±0.14(syst))%. This result does not confirm the evidence for direct CP violation in the charm sector reported in other analyses.